2023
DOI: 10.5187/jast.2023.e88
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Complex Probiotics in Growing-Finishing Pigs and Swine Compost

Kyeongho Jeon,
Minho Song,
Jihwan Lee
et al.

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…2,7 Probiotics are live microbiota that provide health benefits to the host by maintaining the homeostasis of the intestinal microbiota and the immune system and possessing antiinflammatory and anti-aging properties in human and animal. [8][9][10][11][12][13][14][15][16][17][18] Recent studies have shown that Lacticaseibacillus rhamnosus species are probiotics, a type of intestinal bacteria, and have been reported to provide various biological activi-ties: 19 anti-inflammatory, 20 anti-obesity, 21 immune modulation, 22 gut health (IBD and IBS), [23][24][25] and cholesterol level reduction. In addition, the Lacticaseibacillus rhamnosus IDCC3201 strain used in our study was isolated from infant feces, and it has been confirmed to be 18 anti-allergic, 26 antiinflammatory, anti-pathogenic, 19 and immunomodulatory.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Probiotics are live microbiota that provide health benefits to the host by maintaining the homeostasis of the intestinal microbiota and the immune system and possessing antiinflammatory and anti-aging properties in human and animal. [8][9][10][11][12][13][14][15][16][17][18] Recent studies have shown that Lacticaseibacillus rhamnosus species are probiotics, a type of intestinal bacteria, and have been reported to provide various biological activi-ties: 19 anti-inflammatory, 20 anti-obesity, 21 immune modulation, 22 gut health (IBD and IBS), [23][24][25] and cholesterol level reduction. In addition, the Lacticaseibacillus rhamnosus IDCC3201 strain used in our study was isolated from infant feces, and it has been confirmed to be 18 anti-allergic, 26 antiinflammatory, anti-pathogenic, 19 and immunomodulatory.…”
Section: Introductionmentioning
confidence: 99%
“…Among various alternatives to antibiotic substances, such as probiotics, organic acids, bacteriocins, and antimicrobial peptides, we have focused on the potential of bacteriophages as antimicrobial agents (Fig. 1) [9,[14][15][16][17]. In contrast to indiscriminate bombardment by antibiotics, bacteriophages (phages) possess characteristics akin to guided missiles, selectively infecting and killing specific bacteria (Fig.…”
Section: Introductionmentioning
confidence: 99%